Enzymatic completion of mammalian lagging-strand DNA replication. - Turchi, J J (1994)
Using purified proteins from calf and a synthetic substrate, we have reconstituted the enzymatic reactions required for mammalian Okazaki fragment processing in vitro. The required reactions are removal of initiator RNA, synthesis from an upstream fragment to generate a nick, and then ligation. With our substrate, RNase H type I (RNase HI) makes a single cut in the initiator RNA, one nucleotide 5' of the RNA-DNA junction. The double strand specific 5' to 3' exonuclease removes the remaining monoribonucleotide. After dissociation of cleaved RNA, synthesis by DNA polymerase generates a nick, which is then sealed by DNA ligase I. The unique specificities of the two nucleases for primers with initiator RNA strongly suggest that they perform the same reactions in vivo.